Population dataset for 21 simple tandem repeat loci in the Akan population of Ghana - Abban Edward Kofi (Data in Brief, 2020)
Short tandem repeat (STR) loci are widely used as genetic marker for ancestral and forensic analyses. The latter application includes for paternity testing and DNA profiling of samples collected from scenes of crime and suspects. This survey provides the first dataset for 21 STR loci across the Akan population in Ghana by genotyping of 109 unrelated healthy individuals using Investigator 24plex kit. None of the STR loci screened deviated from Hardy-Weinberg equilibrium after applying Bonferroni correction. Overall, 224 unique alleles were observed with allele frequencies ranging from 0.005 to 0.518. The combined match probability, combined power of exclusion and combined power discrimination were 1 in 4.07 × 10−25, 0.999999999 and 1, respectively. Principal coordinate analysis carried out using 21 STR allele frequency data mapped the Akans with Nigerian subpopulation groups (Hausa, Igbo and Yoruba), but separated from Thais of Thailand, Chechen of Jordan and Tijuana of Mexico.